Taking gravity online: the role of virtual proximity in international finance - Christiane Hellmanzik; Martin Schmitz (European Central Bank (ECB), 2016)
This paper analyses international patterns of bilateral portfolio equity and debt investment in a gravity model framework. We contribute to the literature by exploring the role of virtual proximity – measured by bilateral internet hyperlinks between countries – as a novel proxy for cross-border information flows and cultural proximity more generally. Our findings show that bilateral portfolio investment is significantly affected by virtual proximity, indicating that countries which are more closely connected in terms of web content are more integrated financially. The effect is stronger for equity than for debt investment, highlighting the larger information sensitivity of equity investments, and is largest for investments among advanced economies. Moreover, including virtual proximity in estimations reduces the importance of traditionally-used proxies for information asymmetries and cultural proximity.
Keywords: F12; F15; Z10; 330; cultural proximity; hyperlinks; information; international capital flows; internet; portfolio investment